Flow alterations caused by hydropower projects in two Mekong tributary basins: the livelihood implications. [Abstract only]. - Hecht, J.; McCartney, Matthew P.; Lacombe, Guillaume; Vogel, R. (2013)
There is increasing concern over projected changes in the magnitude and timing of streamflow due to the construction of hydropower dams in the Mekong basin and elsewhere. We compare a suite of indicators for their ability to reflect changes from pre-dam flow regimes. Using two case studies, we illustrate the differences in hydrologic alteration that take place downstream of dams that are used for (i) in-stream power production (Nam Ngum 1 Dam) and (ii) diverting water to off-stream production sites (Nam Theun-Hinboun Project). We show that dams for in-stream power production reduce wet season flows, increase dry season flows and attenuate both high- and low-flow extremes. In contrast, dams constructed for off-stream power production mildly reduce flood peaks when diversions are possible during extreme high flow conditions while dry season streamflow declines sharply due to the priority placed on hydropower production. Our analysis summarizes the effects of dams on the frequency, duration, timing and rates of change of discharge at sites downstream of dams. We then review the relevance of metrics of hydrologic alteration for assessing impacts of hydropower dams on livelihoods dependent upon the natural variability of the flow regime in monsoonal climate zones.